2010
DOI: 10.1155/2010/278078
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation by Portable Gas Chromatography: Mass Spectrometry of VOCs Associated with Vapor Intrusion

Abstract: Development of a robust reliable technique that permits for the rapid quantitation of volatile organic chemicals is an important first step to remediation associated with vapor intrusion. This paper describes the development of an analytical method that allows for the rapid and precise identification and quantitation of halogenated and nonhalogenated contaminants commonly found within the ppbv level at sites where vapor intrusion is a concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Recently, the portable GC-MS has been used widely in different applications for VOCs/SVOCs detections, including analysing VOCs/SVOCs in indoor air samples (Hopler, 2012;Leary et al, 2016;Barnes et al, 2004;Shakoor et al, 1997;Fair et al, 2010;Gorder and Dettenmaier, 2011). Unlike conventional benchtop GC-MS systems, which are normally coupled with sample concentrating equipment using thermal desorption.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the portable GC-MS has been used widely in different applications for VOCs/SVOCs detections, including analysing VOCs/SVOCs in indoor air samples (Hopler, 2012;Leary et al, 2016;Barnes et al, 2004;Shakoor et al, 1997;Fair et al, 2010;Gorder and Dettenmaier, 2011). Unlike conventional benchtop GC-MS systems, which are normally coupled with sample concentrating equipment using thermal desorption.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative site investigation techniques can be used to distinguish the background sources from VI (Table ). Portable GC-MS or GC has been successfully used for identifying potential indoor background sources or vapor entry points. ,,,, Another applicable method is building pressure cycling (BPC) which involves manipulation of indoor-outdoor pressure conditions to either induce or suppress VI. ,, Under positive indoor pressure, subsurface VI is minimized and indoor air sampling can be used to characterize the background sources of VI. , A combination of portable GC-MS and BPC has been successfully used to identify indoor background sources at several sites. ,, CSIA has been used to distinguish between background sources and VI. ,, Isotope signatures of VOCs may change over time due to fractionation effects associated with biodegradation or physical processes (e.g., diffusion, volatilization, sorption, and dissolution) . The differences in isotope signatures between subsurface sources and indoor-relevant products can be used to identify the origin of indoor VOCs. ,, CSIA analysis needs a relatively large amount of analyte (e.g., > 1 ng of C), but VOC concentrations in indoor air are relatively low (∼μg/m 3 ).…”
Section: Challenges In Vapor Intrusion Investigation and Decision Makingmentioning
confidence: 99%
“…In this study, instead of employing typical laboratory analytical procedures, such as USEPA Methods TO-14 and TO-15 (Compendium Method TO-15, 1997;Method-14, 1999), a portable gas chromatography-mass spectrometer (GC/MS) was used to determine VOCs in the field. The analysis of VOCs and SVOCs in indoor and outdoor air samples has been extensively used by portable GC/MS in a variety of applications (Shakoor et al, 1997;Barnes et al, 2004;Fair et al, 2010;Gorder and Dettenmaier, 2011;Hopler, 2012;Leary et al, 2016) and the instrument can approach detection limits that satisfy criteria required by environmental protection authorities (EPA). With the fast infield sample preparation and pre-concentration processes, such as employing the solid-phase micro-extraction (SPME) approach to sample conditioning, studies have demonstrated that the portable GC/MS instrument is reliable for rapid in-field quantitative analysis of VOCs for contaminated site vapour intrusion assessment (Hook et al, 2002;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%